Noise-absorbing material composition
By using a variety of carboxylic functional polymers and azacyclopropyl organic compounds with different glass transition temperatures in the absorption material composition, combined with water as a solvent, the problem of narrow effective damping temperature range of traditional damping materials is solved, and absorption material composition with good damping effect at different temperatures is achieved.
Patent Information
- Application Number
- CN202080099683.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-04-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2040-04-14
AI Technical Summary
Traditional damping materials are only made of a single rubber, and their effective damping temperature range is narrow and cannot meet the needs of high-tech fields such as aircraft and rockets. It requires damping materials to have good damping effects at different temperatures.
A sound absorbent material composition is developed, comprising at least two carboxylic functional polymers having different glass transition temperatures (Tg), and at least one organic compound having at least two azecyclopropyl per molecule, and using water as a solvent to form a cured product to expand the effective damping temperature range.
Through the curing product of the absorbent material composition, the temperature range of effective damping is significantly expanded, the performance of the damping material at different temperatures is improved, and the needs of the high-tech field are met.
Smart Images

Figure BDA0003884076270000051 
Figure BDA0003884076270000052 
Figure BDA0003884076270000061
Abstract
Description
Technical Field
[0001] The present invention relates to a sound deadener composition comprising: at least two materials having different glass transition temperatures (T g ) carboxyl functional polymer; at least one organic compound having at least two aziridinyl groups per molecule; and water. The cured product of the muffler material composition according to the present invention exhibits a wider temperature range for effective damping. Background Art
[0002] It is known that damping materials made of rubber are used for vibration reduction and noise reduction. It utilizes the viscoelastic properties of the rubber contained in the composition, through the internal friction caused by the internal molecular motion of the polymer chain, to disperse the mechanical energy generated by external mechanical or sound vibration. Generally, tan δ is an indicator of the effectiveness of the damping capacity of a material, also known as the loss factor. The higher the tan δ, the greater the damping coefficient. The temperature range when the damping material has a high damping coefficient is the effective damping temperature range.
[0003] Damping materials have been widely used in the mechanical field, construction industry, automobile industry, etc. However, traditional damping materials are made of only a single rubber, and their effective damping temperature range is narrow, so they cannot be used in high-tech fields (such as aircraft and rockets), which require damping materials to have good damping effects at different temperatures.
[0004] Therefore, there is a need to develop a sound-absorbing material composition whose cured product has a wider temperature range for effective damping. Summary of the invention
[0005] The present invention relates to a sound-absorbing material composition, comprising:
[0006] a) at least two materials with different glass transition temperatures (T g ) of a carboxyl-functional polymer;
[0007] b) at least one organic compound having at least two aziridine groups per molecule,
[0008] The aziridine groups of the organic compound may be the same or different from each other and are independently represented by structure (I):
[0009] and
[0010] c) water;
[0011] in
[0012] R 1 and R 2 are independently hydrogen or C 1 -C20 An optionally substituted monovalent hydrocarbon group, preferably hydrogen or C 1 -C 10 An optionally substituted monovalent hydrocarbon group, more preferably hydrogen or C 1 -C 4 An optionally substituted monovalent hydrocarbon group.
[0013] The present invention also relates to a cured product of the sound-absorbing material composition.
[0014] The cured product of the sound-absorbing material composition has a wider temperature range for effective damping.
[0015] The present invention also relates to an article coated or filled with a cured product of the sound-absorbing material composition.
[0016] The invention also relates to a preparation method and a curing method of the sound-absorbing material composition. DETAILED DESCRIPTION
[0017] In the following paragraphs, the present invention will be described in more detail. Each aspect described in this way can be combined with any one or more other aspects, unless clearly indicated to the contrary. Particularly, any feature indicated as preferred or advantageous can be combined with any one or more other features indicated as preferred or advantageous.
[0018] In the context of the present invention, the terms used are to be interpreted according to the following definitions, unless the context dictates otherwise.
[0019] As used herein, the singular forms "a," "an," and "the" include singular and plural referents unless the context clearly dictates otherwise.
[0020] As used herein, the terms "comprising" and "including" are synonymous with "containing," "including," or "having" and are inclusive or open-ended and do not exclude additional, unrecited members, elements, or method steps.
[0021] Recitations of numerical endpoints include all numbers and fractions subsumed within the corresponding range, as well as the recited endpoints.
[0022] The entire contents of all references cited in this specification are hereby incorporated by reference.
[0023] Unless otherwise defined, all terms (including technical and scientific terms) used in the process of disclosing the present invention have the meanings commonly understood by ordinary technicians in the field to which the present invention belongs. By way of further guidance, some term definitions are included to better understand the teachings of the present invention.
[0024] In the context of this disclosure, certain terms are used.
[0025] The term "(meth)acrylate" means both or either of "acrylate" and "methacrylate".
[0026] The term "(meth)acrylic" refers to both or either of "acrylic" and "methacrylic".
[0027] The term "ethylenically unsaturated" refers to at least one site of unsaturation that is non-aromatic.
[0028] The term "hydrocarbyl" refers to an organic group consisting of carbon and hydrogen. Examples of hydrocarbyl groups include, but are not limited to, alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, isopropyl, tert-butyl, isobutyl, and similar groups; alkenyl groups such as vinyl, allyl, butenyl, pentenyl, hexenyl, and similar groups; aralkyl groups such as benzyl, phenethyl, 2-(2,4,6-trimethylphenyl)propyl, and similar groups; aryl groups such as phenyl, tolyl, xylyl, and similar groups; or alkylene groups such as methylene, ethylene, propylene, and similar groups.
[0029] The term "optionally substituted" in the term "optionally substituted hydrocarbon group" means that one or more hydrogens on the hydrocarbon group may be replaced by a corresponding number of substituents, wherein the substituents are preferably selected from halogen, nitro, azido, amino, hydroxyl, carbonyl, ester, cyano, sulfide, sulfate, sulfoxide, sulfone and sulfone groups, etc.
[0030] The term "substantially free" means that a material or functional group may be present in incidental amounts, or that a particular event or reaction occurs only to a minor extent that does not affect the desired properties. In other words, the material or functional group is not intentionally added to the composition in question, but may be present at a minor or insignificant level, for example, because it is carried over as an impurity as part of the intended composition components.
[0031] The term "water-soluble" means that the relevant components or ingredients in the composition can be dissolved in the aqueous phase at the molecular level.
[0032] The term "water-dispersible" means that the relevant components or ingredients in the composition can be dispersed in an aqueous phase and form a stable emulsion or suspension.
[0033] The term "glass transition temperature" refers to the temperature at which a polymer transitions between a highly elastic state and a glassy state. The glass transition temperature can be measured, for example, by dynamic mechanical analysis (DMA).
[0034] Carboxyl functional polymers
[0035] The sound-absorbing material composition of the present invention comprises at least two materials with different glass transition temperatures (T g ) of a carboxyl functional polymer. The muffler material composition may include two types of polymers having different T g carboxyl functional polymers, three with different T g of carboxyl functional polymers, or even more polymers with different T g Carboxyl functional polymers with different glass transition temperatures (T g ) are preferably partially compatible or incompatible with each other.
[0036] The carboxyl functional polymer can be any common carboxyl functional polymer as known in the art, and it has at least one carboxyl functional group.Carboxyl functional polymers with different glass transition temperatures are preferably water-soluble or water-dispersible, and are derived from water-soluble monomers or water-dispersible monomers and their combinations, and are optionally derived from water-insoluble monomers.Carboxyl functional polymers with different glass transition temperatures can be obtained by the polymerization of ethylenically unsaturated carboxylic acid monomers in the presence of an initiator. Suitable ethylenically unsaturated carboxylic acid monomers include but are not limited to acrylic acid, glacial acrylic acid, methacrylic acid, isooctyl acrylic acid, crotonic acid, cinnamic acid, maleic acid, 2-methylmaleic acid, isocrotonic acid, fumaric acid, itaconic acid, 2-methylitaconic acid, methacrylic anhydride, isooctyl acrylic anhydride, crotonic anhydride, fumaric anhydride, maleic anhydride and their combinations in any. Suitable initiators may be selected from: peroxide initiators, such as acetyl peroxide, diisopropylbenzene peroxide (DCP), 2,5-dimethyl-2,5-bis(tert-butylperoxy)-hexyne (DBPH), benzoyl peroxide (BPO), bis(2,4-dichlorobenzoyl) peroxide (DCBP), tert-butyl peroxypivalate (BPP), dicyclohexyl peroxydicarbonate (DCPD), potassium persulfate (KSP), ammonium persulfate (ASP), etc.; azo compound initiators, such as 2,2'-azo-bis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azo-bis-isobutyronitrile, azobisisoheptanenitrile, etc.; and persulfate initiators, such as potassium persulfate, sodium persulfate, ammonium persulfate, etc. The initiators may be used alone or in any combination.
[0037] In some embodiments of the present invention, the glass transition temperatures (T g ) preferably has at least two carboxyl functional groups per molecule.
[0038] In some embodiments of the present invention, the glass transition temperatures (T g ) is more preferably water dispersible than water soluble.
[0039] In some embodiments of the present invention, the T of carboxyl-functional polymers having different glass transition temperatures is g The value is preferably in the range of -40 to 60°C, for example -40°C, -30°C, -20°C, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C and 60°C.
[0040] Examples of commercially available carboxyl-functional polymers are, for example, Acousticryl AV 1331, Acoustictryl AV 1220 and Primal SD68 from Dow.
[0041] In some embodiments of the present invention, the sound-absorbing material composition of the present invention has different glass transition temperatures (T g ) is present in an amount of 5 to 35 wt %, and preferably 10 to 25 wt %.
[0042] Organic compounds having at least two aziridine groups
[0043] The sound-absorbing material composition of the present invention comprises at least one organic compound having at least two aziridine groups per molecule. The organic compound having at least two aziridine groups per molecule serves to combine at least two materials having different glass transition temperatures (T g ) are connected to form an interpenetrating polymer network (IPN structure). The mechanism of forming the IPN structure is illustrated as follows:
[0044]
[0045] The aziridine groups of the organic compounds of the present invention may be the same as or different from each other and are independently represented by structure (I):
[0046]
[0047] in
[0048] R 1 and R 2 are independently hydrogen or C 1 -C 20 An optionally substituted monovalent hydrocarbon group, preferably hydrogen or C 1 -C 10 An optionally substituted monovalent hydrocarbon group, more preferably hydrogen or C 1 -C 4 An optionally substituted monovalent hydrocarbon group.
[0049] In some embodiments of the present invention, the organic compound having at least two aziridine groups per molecule is preferably represented by structure (II):
[0050]
[0051] in
[0052] R 1 and R 2 are independently hydrogen or C 1 -C 20 An optionally substituted monovalent hydrocarbon group, preferably hydrogen or C 1 -C 10 An optionally substituted monovalent hydrocarbon group, more preferably hydrogen or C 1 -C 4 an optionally substituted monovalent hydrocarbon group;
[0053] R 3 and R 4 Each independently is C 1 To C 20 An optionally substituted divalent hydrocarbon group, preferably C 1 To C 10 An optionally substituted divalent hydrocarbon group, more preferably C 1 To C 4 an optionally substituted divalent hydrocarbon group;
[0054] R 5 C 1 To C 20 An optionally substituted divalent or polyvalent hydrocarbon group, preferably C 1 To C 10 An optionally substituted divalent or polyvalent hydrocarbon group, more preferably C 1 To C 4 an optionally substituted divalent or multivalent hydrocarbon group; and
[0055] x is an integer of 2-4.
[0056] In some embodiments of the present invention, the organic compound preferably has at least three aziridine groups per molecule.
[0057] Illustrative examples of organic compounds having at least two aziridine groups per molecule include, but are not limited to:
[0058] or
[0059] or
[0060]
[0061] In some embodiments of the present invention, when the loss factor of the cured product of the sound-absorbing material composition is to be improved between 0 and 60° C., R in structure (I) or (II) 1 and R 2Preferably both are hydrogen.
[0062] In some embodiments of the present invention, when the loss factor of the cured product of the sound-absorbing material composition is to be improved between -40 and 0°C, in structure (I) or (II), R 1 and R 2 At least one of them is preferably C 1 -C 20 An optionally substituted monovalent hydrocarbon group, more preferably C 1 -C 10 An optionally substituted monovalent hydrocarbon group, even more preferably C 1 -C 4 An optionally substituted monovalent hydrocarbon group.
[0063] Examples of commercially available organic compounds having at least two aziridine groups per molecule are, for example, XC-103, XC-105 and XC-113 from Shanghai Zealchem Co., Ltd.
[0064] In some embodiments of the present invention, at least two materials have different glass transition temperatures (T g ) and the organic compound having at least two aziridine groups per molecule is preferably in the range of 100:0.5 to 100:50, more preferably in the range of 100:1 to 100:25, and even more preferably in the range of 100:8 to 100:12, so as to better improve the loss factor of the cured product of the sound-absorbing material composition.
[0065] In some embodiments of the present invention, the amount of the organic compound having at least two aziridine groups per molecule in the muffler material composition is 0.1 to 5 wt %, preferably 0.3 to 3 wt %, based on the total weight of the muffler material composition.
[0066] water
[0067] The sound-absorbing material composition of the present invention contains water to adjust the viscosity of the composition. The water of the present invention is preferably purified water.
[0068] In some embodiments of the present invention, the amount of water in the muffler material composition is 10 to 60 wt %, such as 20 wt %, 30 wt %, 40 wt % and 50 wt %, based on the total weight of the muffler material composition.
[0069] Other additives
[0070] The sound-damping material composition may further comprise optional additives. The choice of suitable additives for the sound-damping material composition of the invention depends on the specific intended use of the sound-damping material composition and can be determined in individual cases by a person skilled in the art.
[0071] <Thickener>
[0072] The sound-absorbing material composition of the present invention may further comprise at least one thickener. Exemplary thickeners include, but are not limited to, carboxymethyl cellulose, methyl cellulose, cellulose ether, hydroxyethyl cellulose, polyvinyl ether, polyvinyl alcohol, and sodium polyphosphate. The thickeners may be used alone or in combination.
[0073] Examples of commercially available thickeners are, for example: Arbocel ZZ 8 / 1 from Rettenmaier; CMC type 75A powder from MikroTechnik; Natrosol 250HHR from Ashland Aqualon; and Kelzan xanthan gum from CP Kelco.
[0074] In some embodiments of the present invention, the amount of thickener in the sound-absorbing material composition is 0 to 30 wt %, preferably 0.1 to 1 wt %, based on the total weight of the sound-absorbing material composition.
[0075] <Defoaming agent>
[0076] The sound-absorbing material composition of the present invention may further include at least one defoaming agent. Exemplary defoaming agents include, but are not limited to, silicone-based defoaming agents and acrylic-based defoaming agents. Defoaming agents may be used alone or in combination.
[0077] Examples of commercially available defoamers are, for example: BYK-051, BYK-052, BYK-053, BYK-054, BYK-055 from BYK-Chemie GmbH; DISPARLON 1930N and DISPARLON 1934 from Kusumoto Chemicals, Ltd.; and Foamaster MO NXZ from BASF.
[0078] In some embodiments of the present invention, the amount of the defoaming agent in the sound-absorbing material composition is 0 to 2 wt %, preferably 0.1 to 1 wt %, based on the total weight of the sound-absorbing material composition.
[0079] <Corrosion Inhibitor>
[0080] The muffler material composition of the present invention may further comprise at least one corrosion inhibitor. Exemplary corrosion inhibitors include, but are not limited to, cyclohexylamine, diammonium phosphate, dilithium oxalate, dipotassium oxalate, dipotassium phosphate, phosphoric acid, nickel phosphate, and magnesium phosphate. The corrosion inhibitors may be used alone or in combination.
[0081] Examples of commercially available corrosion inhibitors include, for example: PCG 1201, PCG 1909, and PCG 2390 from Polygon Chemie AG.
[0082] In some embodiments of the present invention, based on the total weight of the sound-absorbing material composition, the amount of the corrosion inhibitor in the sound-absorbing material composition is from 0 to 10% by weight, preferably from 0.1 to 5% by weight.
[0083] <Flame retardant>
[0084] The sound-absorbing material composition of the present invention may further comprise at least one flame retardant. Exemplary flame retardants include, but are not limited to, phosphorus-based plasticizers, aluminum hydroxide, magnesium hydroxide, and expandable graphite. The flame retardants can be used alone or in combination.
[0085] Examples of commercially available flame retardants include, for example: aluminum hydroxide from Shanghai Jianghu Industry Co., Ltd.; ADT 20, ADT 150, and ADT 802 from Shijiazhuang ADT Carbonic Material Factory; and CX150, CX 200, and CX 325 from Qingdao Tianheda Graphite Co., Ltd.
[0086] In some embodiments of the present invention, based on the total weight of the sound-absorbing material composition, the amount of the flame retardant in the sound-absorbing material composition is from 0 to 40% by weight, preferably from 15 to 30% by weight.
[0087] <pH regulator>
[0088] The sound-absorbing material composition of the present invention may further comprise at least one pH regulator. Exemplary pH regulators include, but are not limited to, citric anhydride, alkali metal hydroxides, and buffered organic acid solutions (e.g., acetic acid, glutamic acid, and citric acid). The pH regulators can be used alone or in combination.
[0089] Examples of commercially available pH regulators include, for example: potassium pyrophosphate from Redox Chemicals Pty. Ltd.; and ammonia water from Showa Denko.
[0090] In some embodiments of the present invention, based on the total weight of the sound-absorbing material composition, the amount of the pH regulator in the sound-absorbing material composition is from 0 to 5% by weight, preferably from 0.1 to 2% by weight.
[0091] <Filler>
[0092] The sound-absorbing material composition of the present invention may further comprise at least one filler. Exemplary fillers include, but are not limited to, reinforcing fillers such as fumed silica, precipitated silica, crystalline silica, fused silica, dolomite, and carbon black; fibrous fillers such as asbestos, glass fibers, and filaments; and other fillers such as ground calcium carbonate, colloidal calcium carbonate, magnesium carbonate, barium carbonate, barium sulfate, diatomaceous earth, baked clay, clay, talc, barite, anhydrous gypsum, titanium oxide, bentonite, organic bentonite, iron oxide, aluminum fine powder, flint powder, zinc oxide, active zinc oxide (active zinc flower), mica, zinc oxide (zinc flower), white lead. The fillers may be used alone or in combination.
[0093] Examples of commercially available fillers are, for example: glass fiber 4.5 mm from Saint-Gobain; Muskovit Mica 247 from Ziegler & Co. GmbH; calcium carbonate from Fengxian Bazi Shifen; and AEROSIL R974 available from Evonik Specialty Chemicals (Shanghai) Co, Ltd.
[0094] In some embodiments of the present invention, the amount of filler in the sound-absorbing material composition is 0 to 40 wt %, preferably 5 to 25 wt %, based on the total weight of the sound-absorbing material composition.
[0095] Other optional additives that may be used in the sound-deadening material compositions of the present invention include, but are not limited to: antioxidants; biocides; dyes; pigments; and mixtures thereof.
[0096] In a preferred embodiment, the sound-absorbing material composition comprises:
[0097] 5 to 35 wt % of at least two materials having different glass transition temperatures (T g ) of a carboxyl-functional polymer;
[0098] 0.1 to 5% by weight of at least one organic compound having at least two aziridine groups per molecule;
[0099] 10 to 60% by weight of water;
[0100] 0 to 30% by weight of at least one thickener;
[0101] 0 to 2% by weight of at least one defoaming agent;
[0102] 0 to 10% by weight of at least one filler;
[0103] 0 to 40 wt % of at least one flame retardant;
[0104] 0 to 10 wt % of at least one corrosion inhibitor; and
[0105] 0 to 5 wt % of at least one pH adjuster;
[0106] The weight percentages of all components add up to 100 weight %.
[0107] The sound-absorbing material composition of the present invention can be prepared by the following method: at least two materials having different glass transition temperatures (T g ) and at least one organic compound having at least two aziridine groups per molecule are uniformly mixed in water together with optional additives, such as at least one thickener, at least one pH regulator, at least one filler, at least one flame retardant, at least one corrosion inhibitor and at least one defoamer.
[0108] In some embodiments of the present invention, the sound-absorbing material composition is preferably prepared by the following steps:
[0109] a) mixing at least two materials with different glass transition temperatures (T g ) is mixed with at least one thickener and / or at least one pH adjuster in water to obtain a gel;
[0110] b) adding at least one filler, and / or at least one flame retardant, and / or at least one corrosion inhibitor, and / or at least one defoaming agent to the gel and mixing all these components thoroughly to obtain a pre-mixer; and
[0111] c) adding at least one organic compound having at least two aziridine groups per molecule to the premix and mixing all these components thoroughly under vacuum.
[0112] The sound-absorbing material composition of the present invention can be applied to the surface of the substrate by a doctor blade, a sprayer or an extruder, and allowed to cure at room temperature.
[0113] In some embodiments, curing of the sound-absorbing material composition may include the following steps:
[0114] a) exposing the sound-absorbing material composition to room conditions for 1 to 4 hours;
[0115] b) heating the sound-absorbing material composition at a temperature ranging from 40 to 80° C. for 2 to 6 hours; and
[0116] c) cooling the sound-absorbing material composition and allowing the sound-absorbing material to cure at room temperature for 5 to 10 days.
[0117] The loss factor of the cured product of the sound-absorbing material composition of the present invention can be measured according to GB / T 16406.
[0118] The cured product of the muffler material composition of the present invention has a loss factor of g The cured product of the muffler material composition preferably has a loss factor improvement ratio of not less than 10%, more preferably has a loss factor improvement ratio of not less than 20%, and even more preferably has a loss factor improvement ratio of not less than 40%, compared to a baseline loss factor measured for a cured product of a muffler material composition comprising the same carboxyl-functional polymer but not containing an organic compound having at least two aziridine groups per molecule in the composition.
[0119] Example:
[0120] The present invention will be further described and illustrated with reference to the following examples. These examples are intended to help those skilled in the art to better understand and practice the present invention, but are not intended to limit the scope of the invention. Unless otherwise stated, all numerals in the examples are based on weight.
[0121] Examples 1 to 8
[0122] The following materials were used in the examples.
[0123] water;
[0124] Tetrapotassium pyrophosphate (from Redox Chemicals Pty. Ltd.);
[0125] Arbocel ZZ 8 / 1 (natural cellulose fiber from Rettenmaier);
[0126] Glass fiber (4.5 mm long, from Saint Gobain Vetrotex);
[0127] Acousticryl AV 1331 (acrylic emulsion with a Tg of 16° C., comprising 50 wt % acrylic polymer and 50 wt % water, from Dow);
[0128] Acousticryl AV 1220 (acrylic emulsion with a Tg value of 0°C, containing 50 wt% acrylic polymer and 50 wt% water, from Dow);
[0129] Primal SD68 (acrylic emulsion with a Tg value of -20°C, containing 50 wt% acrylic polymer and 50 wt% water, from Dow);
[0130] XC-103 (trimethylolpropane tris(3-aziridine propionate), from Shanghai Zealchem Co., Ltd.);
[0131] XC-113 (trimethylolpropane tris(2-methyl-1-aziridine propionate), from Shanghai Zealchem Co., Ltd.);
[0132] Foamaster MO NXZ (defoamer, from BASF);
[0133] CMC type 75A powder (carboxymethylcellulose sodium salt, from Mikro Technik);
[0134] Natrosol 250HHR (hydroxyethylcellulose, from Ashland Aqualon);
[0135] Muskovit Mica 247 (mica, from Ziegler & Co. GmbH);
[0136] Muskovit Mica N800 (mica, from Ziegler & Co. GmbH);
[0137] Aluminum hydroxide (from Shanghai Jianghu Industry);
[0138] Calcium carbonate (from Fengxian Bazi Shifen);
[0139] PCG 1201 (corrosion inhibitor from Polygon Chemie); and
[0140] Kelzan xanthan gum (from CP Kelco).
[0141] A sound-absorbing material composition was prepared as an example (Ex.).
[0142] <Ex.1>
[0143] Acousticryl AV 1331 (15 g), Acousticryl AV 1220 (8 g), Primal SD68 (15 g), Arbocel ZZ 8 / 1 (0.6 g), CMC type 75A powder (0.1 g), Natrosol 250HHR (0.1 g), Kelzan xanthan gum (0.1 g), tetrapotassium pyrophosphate (0.3 g) were mixed together in water (4.6 g) by a mixer (EUROATAR 60 digital from IKA) at a speed of 1750 r / min for 30 minutes to obtain a gel.
[0144] Glass fiber (0.8 g), Foamaster MO NXZ (0.1 g), Muskovit Mica 247 (27 g), calcium carbonate (10 g), aluminum hydroxide (15 g) and PCG 1201 (0.3 g) were added to the gel and mixed by a high-speed mixer (SpeedMixer DAC 600.2VAC-P from Flack Tek Inc.) at a speed of 1000 r / min for 30 seconds to obtain a premix.
[0145] The premix was further blended by a high-speed mixer (SpeedMixer DAC600.2VAC-P from Flack Tek Inc.) at a speed of 2000 r / min for 60 seconds under vacuum to obtain a sound-absorbing material composition of Ex. 1.
[0146] The loss factor L of the sound-absorbing material composition of Ex.1 after curing 1 (Baseline loss factor) Measured according to GB / T 16406. B&K equipment was used to test the loss factor, and the cantilever beam method was applied. The test specimen was prepared by applying the silencing material composition of Ex. 1 to the surface of cold-rolled steel (200 mm long, 10 mm wide, and 1 mm thick).
[0147] The sound-absorbing material composition is cured by the following steps:
[0148] a) leaving the sound-absorbing material composition on the cold-rolled steel at room temperature for 2 hours;
[0149] b) heating the sound-absorbing material composition at 60° C. for 4 hours; and
[0150] c) cooling the sound-absorbing material composition and allowing the sound-absorbing material composition to cure at room temperature for 7 days.
[0151] The dimensions of the cured sound-absorbing material composition on the cold-rolled steel were: 2 mm in thickness and 180 mm in free length.
[0152] Loss factor improvement ratio M 1 It is calculated as follows:
[0153] M 1 =(L 1 -L 1 ) / L 1
[0154] <Ex.2>
[0155] Acousticryl AV 1331 (15 g), Acousticryl AV 1220 (8 g), Primal SD68 (15 g), Arbocel ZZ 8 / 1 (0.6 g), CMC type 75A powder (0.1 g), Natrosol 250HHR (0.1 g), Kelzan xanthan gum (0.1 g), tetrapotassium pyrophosphate (0.3 g) were mixed together in water (4.1 g) by a mixer (EUROATAR 60digital from IKA) at a speed of 1750 r / min for 30 minutes to obtain a gel.
[0156] Glass fiber (0.8 g), Foamaster MO NXZ (0.1 g), Muskovit Mica 247 (27 g), calcium carbonate (10 g), aluminum hydroxide (15 g) and PCG 1201 (0.3 g) were added to the gel and mixed by a high-speed mixer (SpeedMixer DAC 600.2VAC-P from Flack Tek Inc.) at a speed of 1000 r / min for 30 seconds to obtain a premix.
[0157] XC-103 (0.5 g) was further added to the premix and mixed by a high-speed mixer (SpeedMixer DAC 600.2VAC-P from FlackTek Inc.) at a speed of 2000 r / min for 60 seconds under vacuum to obtain a sound-absorbing material composition of Ex. 2.
[0158] The sound-absorbing material composition of Ex.2 was cured in the same manner as in Ex.1. The loss factor L of the cured sound-absorbing material composition of Ex.2 was 2 Measure in the same manner as Ex.1.
[0159] Loss factor improvement ratio M 2 It is calculated as follows:
[0160] M 2 =(L 2 -L 1 ) / L 1
[0161] <Ex.3>
[0162] The sound-absorbing material composition of Ex. 3 was prepared in a similar manner to Ex. 2, except that 3.6 g of water was used to prepare the gel and 1 g of XC-103 was added to the gel to form a premix.
[0163] The sound-absorbing material composition of Ex.3 was cured in the same manner as in Ex.1. The loss factor L of the cured sound-absorbing material composition of Ex.3 was 3 Measure in the same manner as Ex.1.
[0164] Loss factor improvement ratio M 3 It is calculated as follows:
[0165] M 3 =(L 3 -L 1 ) / L 1
[0166] <Ex.4>
[0167] The sound-absorbing material composition of Ex. 4 was prepared in a similar manner to Ex. 2, except that 2.6 g of water was used to prepare the gel and 2 g of XC-103 was added to the gel to form a premix.
[0168] The sound-absorbing material composition of Ex. 4 was cured in the same manner as in Ex. 1. The loss factor L of the cured sound-absorbing material composition of Ex. 4 was 4 Measure in the same manner as Ex.1.
[0169] Loss factor improvement ratio M 4 It is calculated as follows:
[0170] M 4 =(L 4 -L 1 ) / L 1
[0171] <Ex.5>
[0172] The sound-absorbing material composition of Ex. 5 was prepared in a similar manner to Ex. 2, except that 1.6 g of water was used to prepare the gel and 3 g of XC-103 was added to the gel to form a premix.
[0173] The sound-absorbing material composition of Ex.5 was cured in the same manner as in Ex.1. The loss factor L of the cured sound-absorbing material composition of Ex.5 was 5 Measure in the same manner as Ex.1.
[0174] Loss factor improvement ratio M 5It is calculated as follows:
[0175] M 5 =(L 5 -L 1 ) / L 1
[0176] <Ex.6>
[0177] Acousticryl AV 1331 (15 g), Acousticryl AV 1220 (8 g), Primal SD68 (15 g), Arbocel ZZ 8 / 1 (0.6 g), CMC type 75A powder (0.1 g), Natrosol 250HHR (0.1 g), Kelzan xanthan gum (0.1 g), tetrapotassium pyrophosphate (0.3 g) were mixed together in water (4.6 g) by a mixer (EUROATAR 60 digital from IKA) at a speed of 1750 r / min for 30 minutes to obtain a gel.
[0178] Glass fiber (0.8 g), Foamaster MO NXZ (0.1 g), Muskovit Mica N800 (27 g), calcium carbonate (10 g), aluminum hydroxide (15 g) and PCG 1201 (0.3 g) were added to the gel and mixed by a high-speed mixer (SpeedMixer DAC 600.2VAC-P from Flack Tek Inc.) at a speed of 1000 r / min for 30 seconds to obtain a premix.
[0179] The premix was further blended by a high-speed mixer (SpeedMixer DAC600.2VAC-P from Flack Tek Inc.) at a speed of 2000 r / min for 60 seconds under vacuum to obtain a sound-absorbing material composition of Ex. 6.
[0180] The sound-absorbing material composition of Ex.6 was cured in the same manner as in Ex.1. The loss factor L of the cured sound-absorbing material composition of Ex.6 was 6 (Baseline loss factor) is measured in the same manner as in Ex.1.
[0181] Loss factor improvement ratio M 6 It is calculated as follows:
[0182] M 6 =(L 6 -L 6 ) / L 6
[0183] <Ex.7>
[0184] Acousticryl AV 1331 (15 g), Acousticryl AV 1220 (8 g), Primal SD68 (15 g), Arbocel ZZ 8 / 1 (0.6 g), CMC type 75A powder (0.1 g), Natrosol 250HHR (0.1 g), Kelzan xanthan gum (0.1 g), tetrapotassium pyrophosphate (0.3 g) were mixed together in water (2.6 g) by a mixer (EUROATAR 60 digital from IKA) at a speed of 1750 r / min for 30 minutes to obtain a gel.
[0185] Glass fiber (0.8 g), Foamaster MO NXZ (0.1 g), Muskovit Mica N800 (27 g), calcium carbonate (10 g), aluminum hydroxide (15 g) and PCG 1201 (0.3 g) were added to the gel and mixed by a high-speed mixer (SpeedMixer DAC 600.2VAC-P from Flack Tek Inc.) at a speed of 1000 r / min for 30 seconds to obtain a premix.
[0186] XC-113 (2 g) was further added to the premix and mixed by a high-speed mixer (SpeedMixer DAC 600.2VAC-P from Flack Tek Inc.) at a speed of 2000 r / min for 60 seconds under vacuum to obtain a sound-absorbing material composition of Ex. 7.
[0187] The sound-absorbing material composition of Ex. 7 was cured in the same manner as in Ex. 1. The loss factor L of the cured sound-absorbing material composition of Ex. 7 was 7 Measure in the same manner as Ex.1.
[0188] Loss factor improvement ratio M 7 It is calculated as follows:
[0189] M 7 =(L 7 -L 6 ) / L 6
[0190] <Ex.8>
[0191] The sound-absorbing material composition of Ex. 8 was prepared in a similar manner to Ex. 7, except that 0.6 g of water was used to prepare the gel and 4 g of XC-113 was added to the gel to form a premix.
[0192] The sound-absorbing material composition of Ex. 8 was cured in the same manner as in Ex. 1. The loss factor L of the cured sound-absorbing material composition of Ex. 8 was 8 Measure in the same manner as Ex.1.
[0193] Loss factor improvement ratio M 8 It is calculated as follows:
[0194] M 8 =(L 8 -L 6 ) / L 6
[0195] The test results of Ex. 1 to 8 are shown in Table 1. The muffler material composition containing XC-103 (Ex. 2 to 5) or XC-113 (Ex. 7 to 8) has a better loss factor than the muffler material composition in Ex. 1 or Ex. 6. When the loss factor of the cured muffler material composition at 10° C. is to be improved, the muffler material composition containing XC-103 is more preferred. When the loss factor of the cured muffler material composition at -10° C. is to be improved, the muffler material composition containing XC-113 is more preferred.
[0196] Table 1. Test results
[0197]
Claims
1. A sound-absorbing material composition comprising: a) at least two materials with different glass transition temperatures (T g ) of a carboxyl-functional polymer; b) at least one organic compound having at least two aziridine groups per molecule, The organic compound having at least two aziridine groups per molecule is represented by structure (II): R 1 and R 2 are independently hydrogen or C1-C 20 an optionally substituted monovalent hydrocarbon group; R 3 and R 4 Each independently is C1 to C 20 an optionally substituted divalent hydrocarbon group; R 5 For C1 to C 20 an optionally substituted divalent or multivalent hydrocarbon group; and x is an integer from 2 to 4; and c) water; wherein the at least two have different glass transition temperatures (T g ) and the organic compound having at least two aziridine groups per molecule is in a weight ratio of 100:1 to 100:
25.
2. The sound-absorbing material composition according to claim 1, wherein R 1 and R 2 are independently hydrogen or C1-C 10 An optionally substituted monovalent hydrocarbon group.
3. The sound-absorbing material composition according to claim 2, wherein R 1 and R 2 Each is independently hydrogen or a C1-C4 optionally substituted monovalent hydrocarbon group.
4. The sound-absorbing material composition according to any one of claims 1 to 3, wherein R 3 and R 4 Each independently is C1 to C 10 An optionally substituted divalent hydrocarbon group.
5. The sound-absorbing material composition according to claim 4, wherein R 3 and R 4 Each is independently a C1 to C4 optionally substituted divalent hydrocarbon group.
6. The sound-absorbing material composition according to any one of claims 1 to 3, wherein R 5 For C1 to C 10 An optionally substituted divalent or polyvalent hydrocarbon group.
7. The sound-absorbing material composition according to claim 6, wherein R 5 It is a C1 to C4 optionally substituted divalent or polyvalent hydrocarbon group.
8. The sound-absorbing material composition according to any one of claims 1 to 3, wherein the carboxyl functional polymers having different glass transition temperatures have a T of -40 to 60°C. g value.
9. The sound-absorbing material composition according to any one of claims 1 to 3, wherein the at least two carboxyl-functional polymers having different glass transition temperatures are partially compatible or incompatible with each other.
10. The sound-absorbing material composition according to any one of claims 1 to 3, wherein the at least two carboxyl-functional polymers having different glass transition temperatures are water-dispersible or water-soluble.
11. The sound-deadening material composition of claim 10, wherein the at least two carboxyl-functional polymers having different glass transition temperatures are water-dispersible.
12. The sound-absorbing material composition according to any one of claims 1 to 3, wherein the organic compound contains at least three aziridine groups per molecule.
13. The sound-absorbing material composition according to claim 1, wherein when the loss factor of the cured product of the sound-absorbing material composition is to be improved between 0 and 60°C, R 1 and R 2 All are hydrogen.
14. The sound-absorbing material composition according to claim 1, wherein when the loss factor of the cured product of the sound-absorbing material composition is to be improved between -40 and 0°C, in structure (II), R 1 and R 2 At least one of them is C1-C 20 An optionally substituted monovalent hydrocarbon group.
15. The sound-absorbing material composition according to claim 14, wherein when the loss factor of the cured product of the sound-absorbing material composition is to be improved between -40 and 0°C, in structure (II), R 1 and R 2 At least one of them is C1-C 10 An optionally substituted monovalent hydrocarbon group.
16. The sound-absorbing material composition according to claim 15, wherein when the loss factor of the cured product of the sound-absorbing material composition is to be improved between -40 and 0°C, in structure (II), R 1 and R 2 At least one of them is a C1-C4 optionally substituted monovalent hydrocarbon group.
17. The sound-absorbing material composition according to any one of claims 1 to 3, wherein the at least two materials have different glass transition temperatures (T g ) and the organic compound having at least two aziridine groups per molecule is in a weight ratio of 100:8 to 100:
12.
18. The sound-absorbing material composition according to any one of claims 1 to 3, wherein At least one thickener, and / or at least one defoaming agent, and / or at least one filler, and / or at least one corrosion inhibitor, and / or at least one pH adjuster, and / or at least one flame retardant are further present in the sound-absorbing material composition.
19. The sound-absorbing material composition according to any one of claims 1 to 3, comprising: 5 to 35 wt % of at least two materials having different glass transition temperatures (T g ) of a carboxyl-functional polymer; 0.1 to 5% by weight of at least one organic compound having at least two aziridine groups per molecule; 10 to 60% by weight of water; 0 to 30% by weight of at least one thickener; 0 to 2% by weight of at least one defoaming agent; 0 to 10% by weight of at least one filler; 0 to 40 wt. % of at least one flame retardant; 0 to 10 wt % of at least one corrosion inhibitor; and 0 to 5 wt % of at least one pH adjuster; The weight percentages of all components add up to 100 weight %.
20. A cured product of the sound-absorbing material composition according to any one of claims 1 to 19.
21. An article coated or filled with a cured product of the sound-absorbing material composition according to claim 20.
22. A method for preparing a sound-absorbing material composition according to any one of claims 1 to 19, comprising the following steps: At least two materials with different glass transition temperatures (T g ) and at least one organic compound having at least two aziridine groups per molecule are uniformly mixed in water together with any additives present.
23. The method of claim 22, wherein the additives are at least one thickener, at least one pH adjuster, at least one filler, at least one flame retardant, at least one corrosion inhibitor, and at least one defoamer.
24. A method for curing a sound-absorbing material composition according to any one of claims 1 to 19, comprising the following steps: a) exposing the sound-absorbing material composition to room conditions for 1 to 4 hours; b) heating the sound-absorbing material composition at 40 to 80° C. for 2 to 6 hours; and c) cooling the sound-absorbing material composition and allowing the sound-absorbing material composition to cure for 5 to 10 days.
Citation Information
Patent Citations
Composition for aqueous coating
JP1995062291A
Resin coated metal panel and production thereof
JP1996207199A